Intensified or Routine Case Finding for Pulmonary Tuberculosis among HIV-Infected Patients: Which is Better? - Hamidreza Tabatabaee; Parvin Afsar-kazerooni; Yousef Alimohamadi; Alireza Hasanabadi; Fatemeh Khavandegaran; Katayoun Tayeri; Abbas Rezaianzadeh; Jafar Hasanzadeh (Shiraz University of Medical Sciences, 2015)
Background: Intensified strategy includes special attention to the symptoms such as cough (more than two weeks), fever (more than three weeks), night sweats (more than three weeks), and weight loss (more than 3 kg per month). If any of the above symptoms was positive, in suspected individuals for TB, more assessment should be done. The aim of this study was to compare between intensified and routine case finding for a better case selection method for diagnosis of pulmonary tuberculosis among HIV-Infected Persons.Methods: The sample size was calculated 237 patients (474 for the two groups). In the current study, the patients were divided randomly into two groups: A) intensified case finding group and B) routine case finding group. Considering the sputum culture as the gold standard, we calculated the sensitivity and specificity, Positive predictive value (PPV), Negative predictive value (NPV) for fever, weight loss, coughing more than two week, night sweats, and PPD test.Result: A total of eight positive cases of tuberculosis were detected in the intensified while four were found in the routine case finding group. Sensitivity, specificity, PPV, and NPV for cough in diagnosis of TB were 25%, 87%, 6%, and 97%, respectively. For weight loss, they were 62.5%, 83%, 10.8%, and 98.5% respectively while these amounts were, 7%, 85%, 97.6, 37.5 for night sweats. For fever, they were, 25%, 92.9%, 10.5%, and 97% respectively, and for PPD they were 87.5%, 40%, 4.6%, and 98.9%, respectively.Conclusion: Key symptom screening, such as cough, fever, weight loss and night sweats, has an important role in detecting TB among HIV-infected patients.